Phase-Aligned Physical-Layer Network Coding in Visible Light Communications - Xun Guan; Qing Yang; Taotao Wang; Calvin Chun-Kit Chan (IEEE Photonics Journal, 2019)
Deploying relay nodes in visible light communication (VLC) relieves the requirement of line-of-sight transmission and thus extends the service coverage of VLC systems. In this paper, we propose to employ physical-layer network coding (PNC) in the VLC system to increase its throughput by boosting the data transmission at the relay node. We design a unified PNC–VLC framework that includes both the physical-layer signal processing algorithm and the medium access control method. To further improve the feasibility, we propose a novel phase-aligning method to counter the phase offset among nodes in practical VLC systems. Experimental results show a throughput improvement of 88.23% by employing the PNC–VLC framework, and the link budget is reduced by 4 dB at a bit error rate of 3.8 × 10−3 by using the phase-aligning method.